EFEKTIFITAS PELAKSANAAN PROGRAM TNI MANUNGGAL MEMBANGUN DESA ( TMMD) DALAM MEWUJUDKAN KETAHANAN WILAYAH - Eny Purwatiningsih (Jurnal Ketahanan Nasional, 2013)
This paper explained the TNI program conduct in village’s building. The qualitative data showed TMMD’s target consisted of physical and additional target and also the non-physical target had been achieved. The TMMD Program conduct’s effectiveness had positive effect on regional resilience. It showed that TMMD Program able to enhanced the unity and unifi cation in the community and able to grew the decreasing togetherness. Therefore the program would be able to strengthened and enhanced the integrated of the TNI and people which would be enhance the people’s wealth, and also strengthened the unifi cation of the TNI and people to supported national’s defense.Keywords: TNI, TMMD, Village’s Building, and Regional Resilience.